RESULT ANALYSIS OF PIPE EXAMINATION AND COMPUTATION USING FLUENT SOFTWARE TO FIND FRICTION COEFFICIENT OF PIPE - NIXON (NIM : 13104132); Pembimbing : Ir. Arianto Santoso, M.sc , WALFREDDY
Friction coefficient at pipe can be known using laboratory testing method and computation method by using Fluent software. in laboratory testing method,pipe is flowed by incompressible fluid, and material of the pipe is copper. The data that we find is a change of pressure in the point of pipe that we want to calculate. After we found the change of pressure, we can find the head loss and also friction coefficient. In computation method, we use fluent software. This software can be used to find friction coefficient of pipe. Things that we have to do is to enter an input data and output data and then we enter the boundary condition of the pipe. Result of friction coefficient with laboratory testing method and computation method is being compared to the copper material table, that we get from literature. The result of laboratory testing method and computation method using fluent software shows that the computation method is closer to the copper pipe material table. The result of laboratory testing method has many errors. One of them is an error in reading. Besides an error in reading, the age of pipe change consideredly that makes calculation result not valid. If we analysed the condition, corrosion inside the pipe can be the dominant factor.